The Andreotti trial. The labile border between direct involvement and third parties in associated crimes (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
By examining an exceptional criminal proceeding in this paper we propose to conduct a study on criminal law ‘in action’ in order to verify the mechanisms of application of two associative offenses (‘simple’ criminal conspiracy and mafia-type criminal conspiracy). As a matter of fact the analysis reconstructs the intense trial about Giulio Andreotti’s working with Cosa Nostra – Andreotti, starting from March 4 1993, is accused of being at first an external competitor and subsequently a participant of Cosa Nostra in connection with a qualitatively complex accusatory apparatus. As a result of this analysis we come to ascertain how fleeting the boundary between the role of partecipant and external competitor in a criminal conspiracy can be, especially in case of political working with mafia-type criminal conspiracy (here Cosa Nostra).Keywords: Andreotti, Cosa Nostra, grey area, associative offenses, fake news